Cellular Distribution of Canonical and Putative Cannabinoid Receptors in Canine Cervical Dorsal Root Ganglia - Chiocchetti, Roberto; Galiazzo, Giorgia; Tagliavia, Claudio; Stanzani, Agnese; Giancola, Fiorella; Menchetti, Marika; Militerno, Gianfranco; Bernardini, Chiara; Forni, Monica; Mandrioli, Luciana (Frontiers in Veterinary Science, 2019)
Growing evidence indicates cannabinoid receptors as potential therapeutic targets for chronic pain. Consequently, cannabinoid receptor agonists might have a role in medicine and are now being developed to be used in human and veterinary patients in pain. To better understand the actions of a drug, it is of paramount importance to know the cellular distribution of its specific receptor(s). The distribution of canonical and putative cannabinoid receptors in the peripheral and central nervous system of dogs is still in its infancy. In order to help fill this anatomical gap, the present ex vivo study has been designed to identify the cellular sites of cannabinoid and cannabinoid-related receptors in canine spinal ganglia. In particular, the cellular distribution of the cannabinoid receptors type 1 and 2 (CB1 and CB2) and putative cannabinoid receptors G protein-coupled receptor 55 (GPR55), nuclear peroxisome proliferator-activated receptor alpha (PPARα), and transient receptor potential vanilloid type 1 (TRPV1) have been immunohistochemically investigated in the C6-C8 cervical ganglia of dogs. Faint CB1 receptor immunoreactivity was observed in small-sized neurons, whereas Schwann cells, blood vessel smooth muscle cells, and pericyte-like cells brightly expressed CB2 receptor immunoreactivity. Bright GPR55 receptor immunoreactivity was expressed by satellite glial cells (SGCs) whereas neurons of different size showed faint to moderate immunolabeling. PPARα immunoreactivity was expressed by SGCs and endothelial blood vessels. TRPV1 immunoreactivity was expressed by neurons and nerve fibers of different size. The present study may represent a morphological substrate to consider in order to develop therapeutic strategies against chronic pain